Adolescents' Lockdown-Induced Coping Experiences (ALICE) Study: A Qualitative Exploration of Early Adolescents' Experiences of Lockdown and Reintegration. (April 2022) - Ashworth, Emma; Hunt, Anna; Chopra, Jennifer; Eames, Catrin; Putwain, David W.; Duffy, Kathryn; Kirkby, Joanna; McLoughlin, Shane; Saini, Pooja
The aim of this study was to explore the experiences and perceived impact of the COVID-19 lockdowns among early adolescents in the northwest of England, as well as explore the self-care and coping strategies that helped the young people continue to thrive. Fourteen adolescents, 9 boys and 5 girls, were recruited from four secondary schools in North West England. Remote online interviews were conducted. Inductive reflexive thematic analysis was used to analyse the interview data and four themes were identified: (1) change: 'life feels weird'; (2) embracing lockdown; (3) feelings of loss; and (4) stress, worry and challenge. Processes identified will be able to help inform policy and practice for supporting adolescents in the future, including the promotion of positive coping strategies and the provision of resources for young people, schools and families.